𝒩-Structures Applied to Closed Ideals in BCH-Algebras. (15th March 2010) - Jun, Young Bae; Öztürk, Mehmet Ali; Roh, Eun Hwan
Abstract : The notions of 𝒩 -subalgebras and 𝒩 -closed ideals in BCH-algebras are introduced, and the relation between 𝒩 -subalgebras and 𝒩 -closed ideals is considered. Characterizations of 𝒩 -subalgebras and 𝒩 -closed ideals are provided. Using special subsets, 𝒩 -subalgebras and 𝒩 -closed ideals are constructed. A condition for an 𝒩 -subalgebra to be an 𝒩 -closed ideal is discussed. Given an 𝒩 -structure, the greatest 𝒩 -closed ideal which is contained in the 𝒩 -structure is established.